1973
DOI: 10.1002/hlca.19730560408
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Formation of the D‐Penicillamine‐Antigenic Determinant from Penicilloyl Compounds

Abstract: Summavy. The formation of D-penicillamine-L-cystcine mixed disulfide from benzylpenicilloic acid, benzylpenilloic acid and benzylpenicilloyl amide derivatives in 1.-cysteine suspensions a t pH 7,6 and 37" was studied. Thc reaction is faster than direct penicilloylation of proteins known to be a route to penicilloyl antigenic determinants. The production of S-bound penicillamine on protein from penicilloyl compounds must therefore definitely be considered as a potential antigenforming step. The reaction may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A possible explanation is that the adducts resulted from other nucleophiles such as serine, histidine, and cysteine may be too labile to be detected under current analytical conditions or a further transacylation may have occurred (Tsuji et al, 1975). In addition, only penicilloyl lysyl antigenic determinants were detected in this study; minor determinants, such as penicillanyl and penicillamine derivatives (Levine, 1960;Schneider et al, 1973), were not observed. It has been shown that some patients are more sensitive to the minor determinants (Weltzien and Padovan, 1998).…”
Section: Discussionmentioning
confidence: 64%
“…A possible explanation is that the adducts resulted from other nucleophiles such as serine, histidine, and cysteine may be too labile to be detected under current analytical conditions or a further transacylation may have occurred (Tsuji et al, 1975). In addition, only penicilloyl lysyl antigenic determinants were detected in this study; minor determinants, such as penicillanyl and penicillamine derivatives (Levine, 1960;Schneider et al, 1973), were not observed. It has been shown that some patients are more sensitive to the minor determinants (Weltzien and Padovan, 1998).…”
Section: Discussionmentioning
confidence: 64%
“…Given the facile disproportionation that can occur under more basic conditions, only acidic medium should be employed when working with unsymmetrical disulfides in aqueous solutions. While the unsymmetrical disulfides 2-MESSC [27], 3-MPASSC [28], PENSSC [29], and GSSC [30] have been previously synthesized, the CSSCN route appears to be superior from the perspectives of chemical yields and the simplicity of the procedure. Furthermore, since thiocyanogen is very selective for thiols, we anticipate no serious limitations of the procedure we have outlined, provided the reacting thiol is water-soluble and stable in 1 M acid.…”
Section: Discussionmentioning
confidence: 99%